(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: This study was done to observe the high resolution sonographic echo-pattern of the thyroid gland among the non-nodular goitrous patients having abnormal thyrotropin (TSH) level at their first diagnosis. Method: This study was conducted at the Institute of Nuclear medicine and Allied Sciences, Rajshahi, Bangladesh during the period between 1st January, 2014 and 31st March, 2015. The goitrous patients are referred at this Institute by the clinicians for radionuclide thyroid scan, HRUS of thyroid gland and thyroid function tests. Under the basis of convenient sampling technique, 62 patients are included as sample. Their age, gender, HRUS echo-patterns of goiter and thyrotropin levels are recorded and analyzed with statistical software IBM SPSS v. 16. Results: Among the total enrolled patients (n=62), 57 (91.9 %) were female and five (8.1 %) were male. Mean (± SD) age was 28 ± 11.85 years (range=8 to 69 years). Regarding thyrotropin level among the sample patients (n=62), 53 (85.5 %) had above normal range and 9 (14.5 %) had below normal range. In relation to sonographic echo-pattern of the non-nodular goitrous patients (n=62), 43 (69.4 %) had hypoechoic feature, 15 (24.2 %) had non-homogenous feature and four (6.5 %) had both hypoechoic and non-homogenous feature. Among the 43 goitrous patients with hypoechoic feature, 38 had thyrotropin above normal range and five had below normal range; among the 15 goitrous patients with non-homogenous feature, 12 had thyrotropin above normal range and three had below normal range and among the four goitrous patients with both hypoechoic and non-homogenous feature, three had thyrotropin above normal range and one had below normal range. Conclusion: The results of this study will be helpful in the relevant prospective studies which will be concerned with developing non-nodular goiter management algorithm, in addition to the role of other parameters like thyroid function tests especially thyrotropin level, circulating thyroid autoantibodies detection and fine needle aspiration biopsy (FNAB) cytology findings. Bangladesh J. Nuclear Med. 18(2): 152-155, July 2015